THE GODFATHER: A STUDY ON HOW ORGANISED CRIME FAMILIES BECAME A PART OF AMERICAN DREAM - MATHEW, MITHUN; PURUSHOTHAMAN , KAVYA (International Journal of Psychosocial Rehabilitation, 2020)
Organised crime is a complex of mighty enterprises set up for the sole purpose of engaging in illegal activities. A criminal organisation family can also be referred to as a mafia. The families govern over failed states that has no proper educational system, law enforcement and teeming with poverty. Organised crime families make use of these conditions to recruit and indulge in illegal activities such as extortion, robbery, gambling, and prostitution. These crime families have its merits and demerits. While on one side, they deal with illegal activities, on the other they maintain peace within the failed state and follow many family values that contrasts greatly with their activities. The protagonist family Corleones indulge themselves with illegal activities yet has the respect of numerous people, both ordinary and people with power due to the way they conduct their business. This paper will focus on the study of these family values and the way the Corleones conducted their business that made them stand apart from other Crime families on the basis of the 1972 film The Godfather, directed by Francis Ford Coppola